Case for diagnosis. Diffuse ulcerated nodular lesions - Paulo Henrique Teixeira Martins; Gabriela Dallagnese; Laura Luzzatto; Manuela Lima Dantas (Sociedade Brasileira de Dermatologia, 2019)
Abstract Langerhans cell histiocytosis is a rare clonal proliferative disease, characterized by the infiltration of one or multiple organs by histiocytes. Due to the diversity of signs and symptoms, the diagnosis of this disease is often late. The estimated incidence in adults is one to two cases per million, but the disease is probably underdiagnosed in this population. This report presents a case of disseminated Langerhans cell histiocytosis. The authors highlight the most characteristic aspects of this rare and heterogeneous disease, which usually presents as a challenging clinical diagnosis.